The protective effect of Nigella sativa against cisplatin-induced nephrotoxicity in rats - Sara Hosseinian; Abolfazl Khajavi rad; Mousa-; Nema Mohamadian Roshan; Shahrzad Havakhah; Somayeh Shafiee (Mashhad University of Medical Sciences, 2016)
Objective: The clinical use of cisplatin is highly restricted, because of its nephrotoxicity.In this study the protective effect of Nigella sativa (N. sativa) against cisplatin-induced nephrotoxicity was investigated in rats. Materials and Methods: In the current study, the effects of the administration of aqueous-ethanolic extract of N. sativa (100 and 200 mg/kg, BW) and vitamin E (100 mg/kg, BW) against blood and urine biochemical alterations and kidney function in rats treated with cisplatin were investigated. Cisplatin was injected at a dose of 6 mg/kg, BW, on the sixth day of the experiment. Results: The results indicated significant changes in serum urea and creatinine concentration, urine glucose concentration, and urine output in cisplatin group compared with control group. Serum urea and creatinine concentration in preventive and preventive+treatment vitamin E and preventive+treatment N. sativa (200 mg/kg, BW) groups and also serum creatinine concentration in preventive+treatment N. sativa (100 mg/kg, BW) group significantly decreased compared with cisplatin group. Urine glucose concentration in preventive and preventive+treatment N. sativa groups and urine output in preventive and preventive+treatment N. sativa (200 mg/kg, BW) groups significantly decreased compared with cisplatin group.Osmolarity excretion rate in preventive and preventive+treatment vitamin E and preventive N. sativa groups was significantly higher than control group. Conclusions: The current study suggests that N. sativa extract and vitamin E in a dose- and time-dependent manner improved the serum and urine biochemical parameters and kidney function in cisplatin-induced nephrotoxicity in rats. However, it needs more investigations to determine the mechanism of N. sativa action on cisplatin-induced kidney toxicity.